2018
DOI: 10.1093/jeg/lby012
|View full text |Cite
|
Sign up to set email alerts
|

Networks and migrants’ intended destination

Abstract: Networks and Migrants' Intended Destination * Social networks are known to influence migration decisions, but connections between individuals can hardly be observed. We rely on individual-level surveys conducted by Gallup in 147 countries that provide information on migration intentions and on the existence of distance-one connections for all respondents in each of the potential countries of intended destination. The origin-specific distribution of distance-one connections from Gallup closely mirrors the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 38 publications
2
66
0
1
Order By: Relevance
“…Aspirations and intentions to migrate have been analysed from both qualitative and quantitative angles (Docquier et al, ; Thulin and Vilhelmson, ; Gubert and Senne, ; Van Hear et al, ; Carling and Schewel, ; Carling and Collins, ; Dao et al, ; Williams et al, ). Many quantitative studies have tapped into the Gallup World Poll (among others, see Esipova et al, ; Docquier et al, ; Esipova et al, ; Cai et al, ; Bertoli and Ruyssen, ; Dao et al, ; Tjaden et al, ), but other examples have focused on, e.g. Latinobarometro, Arab Barometer (Graham and Markowitz, ; Falco and Rotondi, ), or ad hoc surveys (van Dalen, Groenewold, and Fokkema, ; van Dalen, Groenewold, and Schoorl, ; Williams et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspirations and intentions to migrate have been analysed from both qualitative and quantitative angles (Docquier et al, ; Thulin and Vilhelmson, ; Gubert and Senne, ; Van Hear et al, ; Carling and Schewel, ; Carling and Collins, ; Dao et al, ; Williams et al, ). Many quantitative studies have tapped into the Gallup World Poll (among others, see Esipova et al, ; Docquier et al, ; Esipova et al, ; Cai et al, ; Bertoli and Ruyssen, ; Dao et al, ; Tjaden et al, ), but other examples have focused on, e.g. Latinobarometro, Arab Barometer (Graham and Markowitz, ; Falco and Rotondi, ), or ad hoc surveys (van Dalen, Groenewold, and Fokkema, ; van Dalen, Groenewold, and Schoorl, ; Williams et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the role of networks in facilitating immigration is well-known (Beine et al, 2011), having a relative or friend abroad has also been found to increase the attractiveness of a country for potential migrants (Bertoli and Ruyssen, 2018;Manchin and Orazbayev, 2018). Manchin and Orazbayev show that the role of networks is stronger when friends and family who are abroad also send remittances (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study takes a new approach by making use of a subjective measure of gender discrimination to examine both migration intentions and further migration behavior regardless of destination. Unlike most studies disentangling the impact of gender imbalances on migration, we mostly rely on a micro level dataset and exploit the variation across individuals for a large number of countries (see also Bertoli and Ruyssen, 2016;Dustmann and Okatenko, 2014;Manchin and Orazbayev, 2016). The newly available GWP provide a unique and largely unexplored database on individual migration decisions as well as perceptions of gender discrimination and respondents' economic and demographic characteristics for 148 countries in the world between 2009 to 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Ecuadorians have been concentrated in very few countries (see Table 2), a result that holds for many other cases (Bertoli and Ruyssen, 2018). Therefore, the network across the borders is not extensive, which increases the probability of one or at most two distance-one connections among migrants and intending migrants.…”
Section: The Ecuadorian Casementioning
confidence: 99%